2010
DOI: 10.1016/j.cbi.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Pro-2-PAM therapy for central and peripheral cholinesterases

Abstract: Novel therapeutics to overcome the toxic effects of organophosphorus (OP) chemical agents are needed due to the documented use of OPs in warfare (e.g. 1980-1988 Iran/Iraq war) and terrorism (e.g. 1995 Tokyo subway attacks). Standard OP exposure therapy in the United States consists of atropine sulfate (to block muscarinic receptors), the acetylcholinesterase (AChE) reactivator (oxime) pralidoxime chloride (2-PAM), and a benzodiazepine anticonvulsant to ameliorate seizures. A major disadvantage is that quatern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 20 publications
0
32
1
Order By: Relevance
“…With these results, we conclude that pro-2-PAM can be a potential candidate for protection against seizure induced by OP inhibited AChE, and that BBB oxime therapeutics are needed as next generation treatments for OP. In contrast (DeMar et al, 2010;Shih et al, 2011) 2-PAM did not show protection against seizures induced by OP compounds in these studies.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…With these results, we conclude that pro-2-PAM can be a potential candidate for protection against seizure induced by OP inhibited AChE, and that BBB oxime therapeutics are needed as next generation treatments for OP. In contrast (DeMar et al, 2010;Shih et al, 2011) 2-PAM did not show protection against seizures induced by OP compounds in these studies.…”
Section: Discussioncontrasting
confidence: 68%
“…Nanoparticles, which penetrate the BBB are also another attractive carrier to deliver the quaternary oximes to the CNS, but to date has not been shown to enter the CNS in a pharmacologically relevant time (Wagner et al, 2010). Our group have (DeMar et al, 2010) clearly demonstrated that pro-2-PAM, unlike 2-PAM, protected guinea pigs from DFP induced seizure, restored CNS AChE activity, and protected the animal from neuronal death in hippocampus. When pro-2-PAM treatment occurred immediately after OP exposure, pro-2-PAM provided protection against soman.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Of many novel oximes synthesized and evaluated to date, only a few types have shown the potential to cross the BBB. These include pro-drug analogs of PAM (21), phenoxyalkyl pyridinium, detergent-like oximes (22), conjugation of various pyridinium aldoximes to a glucose C-6 Sox transporter (23), various nucleophiles that encompass association with the active center and peripheral site on AChE (24–26) and low molecular weight zwitterions, whose neutral species enables rapid blood-brain barrier passage (27,28). …”
Section: Introductionmentioning
confidence: 99%
“…Although 2-PAM is an effective reactivator, one major deficiency is its inability to cross the blood-brain-barrier (BBB), thus preventing it from reactivating vital OP-inhibited AChE in the central nervous system (CNS). Over the last decade efforts have focused on screening and identifying other reactivating oximes that have a higher BBB permeability while still retaining a high reactivation profile (DeMar et al, 2010; GarcĂ­a et al, 2010; Sit et al, 2011; Radic et al, 2012; Radic et al, 2013; Okolotowicz et al, 2014). In recent work by Radic et al, a promising centrally active oxime reactivator (RS194B, 4, Fig 1.)…”
Section: Introductionmentioning
confidence: 99%